Association between systemic inflammation indicators and psoriasis: a cross-sectional study from NHANES - Xiong, Huizi; Yu, Zengyang (Frontiers in Immunology, 2025)
ObjectivesTo Investigate the association between systemic inflammatory indicators and psoriasis in the adult population of the United States.MethodsWe analyzed data from 16,575 adults in the National Health and Nutrition Examination Survey (NHANES) from 2003–2006 and 2009–2014. Six inflammatory ratios—neutrophil percentageto-albumin ratio (NPAR), neutrophil-to-lymphocyte ratio (NLR), neutrophil-to-high-density lipoprotein cholesterol ratio (NHR), lymphocyte-to-high-density lipoprotein cholesterol ratio (LHR), platelet-to-high-density lipoprotein cholesterol ratio (PHR), and monocyte-to-high-density lipoprotein cholesterol ratio (MHR). Furthermore, subgroup analyses were performed to investigate whether these results remained true among various demographic groups. Finally, the predictive efficacy of inflammatory indicators was assessed through AUC values and ROC curves.ResultsAmong the study participants, 432 (2.6%) had psoriasis. There was a remarkable positive association found between psoriasis and NLR, NHR, and NPAR. After adjusting for various confounding factors, it was found that each 10-unit increase in NPAR was associated with a 90% higher chance of developing psoriasis (OR=1.90, 95% CI 1.11-3.26). Similarly, the odds of psoriasis prevalence increased by 10% for every unit rise in NLR (OR=1.10, 95% CI 1.12-1.18). After full adjustment, however, there was no discernible distinction between psoriasis and NHR (OR=1.03, 95% CI 0.98-1.08). Furthermore, the study identified a nonlinear relationship between psoriasis and systemic inflammation indicators like NPAR, NLR, and NHR, with specific breakpoints at 16.386, 3.269, and 4.286, respectively. Subgroup analysis provided additional evidence that this association remained consistent for different demographic groupings. ROC analysis demonstrated that NLR and NPAR showed better accuracy in predicting psoriasis prevalence.ConclusionThe study indicates a positive affiliation between NPAR, NLR, and the occurrence of psoriasis. Nevertheless, to confirm these discoveries and investigate the underlying mechanisms, more extensive prospective research is necessary.